Pancreatico-broncho-pleural fistula as a complication of acute pancreatitis. - Grossman, A; Jackson, B; Thompson, R; Braimbridge, M (1978)
A case of pancreaticobronchopleural fistula following biopsy of the pancreas is described. This is the second reported case unassociated with a prior fistulous tract to the exterior, and the first demonstrated radiologically. The importance of recognising this rare complication and of treating it surgically is emphasized.